Ff-nano, short functionalized nanorods derived from Ff (f1, fd, or M13) filamentous bacteriophage - Sattar, Sadia; Bennett, Nicholas J.; Wen, Wesley X.; Guthrie, Jenness M.; Blackwell, Len F.; Conway, James F.; Rakonjac, Jasna (Frontiers in Microbiology, 2015)
F-specific filamentous phage of Escherichia coli (Ff: f1, M13 or fd) are long thin filaments (860 nm x 6 nm). They have been a major workhorse in display technologies and bionanotechnology; however, some applications are limited by the high length-to-diameter ratio of Ff. Furthermore, use of functionalized Ff outside of laboratory containment is in part hampered by the fact that they are genetically modified viruses. We have now developed a system for production and purification of very short functionalized Ff-phage-derived nanorods, named Ff-nano, that are only 50 nm in length. In contrast to standard Ff-derived vectors that replicate in E. coli and contain antibiotic-resistance genes, Ff-nano are protein DNA complexes that cannot replicate on their own and do not contain any coding sequences. These nanorods show an increased resistance to heating at 70 °C in 1 % SDS in comparison to the full-length Ff phage of the same coat composition. We demonstrate that functionalized Ff-nano particles are suitable for application as detection particles in sensitive and quantitative “dipstick” lateral flow diagnostic assay for human plasma fibronectin.